2001
DOI: 10.1002/mrd.1046
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of an immortalized human oviductal cell line

Abstract: Human oviductal cells stimulate embryo development in vitro partly by the production of embryotrophic glycoproteins. The identity of these glycoproteins is not yet known mainly because oviductal samples are limited and that the cultured parental oviductal cells cannot produce sufficient amount of embryotrophic factors for characterization. In this study, human oviductal epithelial cells (OE) were immortalized by HPV 16 E6/E7 open reading frame (ORF) by retroviral expression. The characteristics of this immorta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 38 publications
2
40
0
Order By: Relevance
“…The variation in the gene expression of the immortalized oviductal cells could be associated with increasing number of cell passages. In this connection, the telomerase activity of the immortalized cells increases with increasing number of cell passages (13). The observation that exogenous iC3b alone can stimulate embryo development to the greatest extent indicates that the molecule is the actual active embryotrophic molecule.…”
Section: Table II Effects Of C3 and Its Fragments On Mouse Embryo Devmentioning
confidence: 96%
“…The variation in the gene expression of the immortalized oviductal cells could be associated with increasing number of cell passages. In this connection, the telomerase activity of the immortalized cells increases with increasing number of cell passages (13). The observation that exogenous iC3b alone can stimulate embryo development to the greatest extent indicates that the molecule is the actual active embryotrophic molecule.…”
Section: Table II Effects Of C3 and Its Fragments On Mouse Embryo Devmentioning
confidence: 96%
“…OE-E6/E7 cells 22 were maintained in DMEM/F12 medium supplemented with 10% fetal bovine serum (growth medium) in 5% CO 2 at 37°C. Cells were seeded at 500,000 cells per well in 12-well dishes and incubated for 24 hours.…”
Section: Treatment Of Oe-e6/e7 Cell Line With Cotinine and The Nachr␣mentioning
confidence: 99%
“…The homology comparisons also showed that there were 40-50% smilarities between rabbit oviductin and some enzymes of chitinase gene family, but the oviductins showed no chitinase activity [14]. In recent years, few researches concerning the roles of oviductins in the development of early embryo were reported [15], [16].…”
Section: Discussionmentioning
confidence: 91%